RJVs and Price Collusione under Endogenous Product Differentiation - Luca Lambertini; Sougata Poddar; Dan Sasaki (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
We characterise the interplay between firms' decisions in product development, be it joint or independent, and their ensuing repeated price behaviour, either collusive or Bertrand- Nash. Firms face a choice between participating in a joint venture inventing a single product, and in independent ventures developing their respective products which can be either horizontally or vertically differentiated. We prove that joint product development and the resulting lack of horizontal product differentiation may destabilise collusion, whilst firms' R&D decisions have no bearings on collusive stability in the vertical differentiation setting. We also discover the non-monotone dependence of firms' venture decisions at the development stage upon their intertemporal preferences, as well as upon consumers' willingness to pay.
Keywords: 330